Stili mišljenja pri knjižničarjih v splošnih in specialnih knjižnicah v ljubljanski regiji - Senica, Simona (Knjižnica, 2005)
The paper presents Sternberg's theory of mental self-government that makes an unique contribution to the understanding of human individual differences. In order to investigate individual differences of librarians in public and special libraries in the Ljubljana region, the Thinking Styles Inventory was applied to determine the styles of thinking according to Sternberg's theory of mental self-government. Building on the acquired data, some differences in styles of thinking in regard to demographic variable are highlighted. The results point out that the profile of thinking styles of librarians shows high levels for the external and liberal thinking styles, and modest levels for internal, conservative, global and local thinking styles. Some comparisons with other studies are drawn, and a few proposals for further research on the individual differences are suggested.
Keywords: knjižničarji; mišljenje; stili mišljenja; splošne knjižnice; specialne knjižnice; Ljubljana